2019
DOI: 10.1186/s42155-019-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of interventional radiology among medical students at an Indian institution

Abstract: Purpose: Interventional radiology (IR) is a novel and evolving sub-specialty that encompasses image guided diagnostic and therapeutic procedures. With the advent of new imaging techniques and an increasing demand of minimally invasive procedures, IR continues to grow as a core component in medical and surgical therapeutics. Radiology teaching is a part of medical undergraduate curriculum; however, the medical undergraduate cohort lacks exposure to IR principles, methods and techniques. The purpose of this stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…This varied from 15 to 73% in six previous studies in literature conducted at single institutions globally from 2009 to 2019. 3 5 7 8 10 12 There is a steady rising trend of interest for IR among medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This varied from 15 to 73% in six previous studies in literature conducted at single institutions globally from 2009 to 2019. 3 5 7 8 10 12 There is a steady rising trend of interest for IR among medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have established this fact and further pointed out that this might discourage medical graduates in future, not only in choosing IR as a career but also in considering it as an alternative management option within their chosen subspecialty. 5 6 7 8 9 Also, many studies have underlined the positive outcomes of introduction of an undergraduate IR curriculum. 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Alnajjar et al observed that only 25% of Saudi medical students completed or were planning to complete an elective in IR. Finally, Agrawal et al noted an alarmingly low rate of IR rotation completion at 5.7% among Indian medical students [3,34,35]. Students who had a previous rotation in IR tended to be more informed about the specialty [3].…”
Section: Discussionmentioning
confidence: 99%
“…With the arrival and adoption of the latest imaging techniques and the growing demand for image-guided minimally invasive surgical procedures, interventional radiology (IR) has shown steady growth as a core element in medical and surgical therapeutics. However, a lacuna of teaching principles of IR, methods and techniques in the medical undergraduate curriculum was recognized[ 37 ]. Radiology has seen a digital revolution in the past decade having a notable impact on the education and training of radiologists.…”
Section: Radiology Teaching/training In Under- and Post-graduate Educationmentioning
confidence: 99%